Preliminary Results of Bedaquiline as Salvage Therapy for Patients With Nontuberculous Mycobacterial Lung Disease - Philley, Julie V; Wallace, Jr, Richard J; Benwill, Jeana L; Taskar, Varsha; Brown-Elliott, Barbara A; Thakkar, Foram; Aksamit, Timothy R; Griffith, David E (Chest, 2015)
Bedaquiline is an oral antimycobacterial agent belonging to a new class of drugs called diarylquinolines. It has low equivalent minimal inhibitory concentrations for Mycobacterium tuberculosis and nontuberculous mycobacterial (NTM) lung disease, especially Mycobacterium avium complex (MAC) and Mycobacterium abscessus (Mab). Bedaquiline appears to be effective for the treatment of multidrug-resistant TB but has not been tested clinically for NTM disease. We describe a case series of off-label use of bedaquiline for treatment failure lung disease caused by MAC or Mab. Only patients whose insurance would pay for the drug were included. Fifteen adult patients were selected, but only 10 (six MAC, four Mab) could obtain bedaquiline. The 10 patients had been treated for 1 to 8 years, and all were on treatment at the start of bedaquiline therapy. Eighty percent had macrolide-resistant isolates (eight of 10). The patients were treated with the same bedaquiline dosage as that used in TB trials and received the best available companion drugs (mean, 5.0 drugs). All patients completed 6 months of therapy and remain on bedaquiline. Common side effects included nausea (60%), arthralgias (40%), and anorexia and subjective fever (30%). No abnormal ECG findings were observed with a mean corrected QT interval lengthening of 2.4 milliseconds at 6 months. After 6 months of therapy, 60% of patients (six of 10) had a microbiologic response, with 50% (five of 10) having one or more negative cultures. This small preliminary report demonstrates potential clinical and microbiologic activity of bedaquiline in patients with advanced MAC or Mab lung disease but the findings require confirmation with larger studies.